POLA PEMILIHAN BAHASA BERDASARKAN PERISTIWA BAHASA DAN KATEGORI UMUR: KASUS PEMILIHAN BAHASA ETNIK BUGIS PERANTAU DALAM RANAH KELUARGA DI KABUPATEN DONGGALA - Tamrin Tamrin (TELAGA BAHASA, 2017)
The social interaction in multilingual societies and the availability of multiple languages requires each speaker to have the ability to precisely choose the language or variety of languages which appropriate to the communication situation. By raising the case of language selection patterns based on language events and age categories in the language selection of Bugis ethnic in Donggala Regency, this study aimed to (1) describe the pattern of language selection in family domain of Bugis ethnic based on the language event and age category, and (2) analyse the factors underlying the selection of languages based on the language event and age category. The method used is a sociolinguistic approach with questionnaires, interviews, observations, and recording techniques, then the data had been analyzed based on the percentage pattern of the language selection. The result indicated that Bugisnese ethnic in Donggala Regency still chooses Bugisnese language as their communication tool n based on the event of language and age category. The Age of 28-49 and 50 years and above strongly maintain and choose to use Bugisnese language, while among the 11-15 years old and above the use of Bugis language are beginning to decline.